Peran Sejarah Walisongo Dalam Pengembangan Model Moderasi Beragama - Yunita, Intan; Shanie, Arsan; Amaliya, Izana; Maretta, Carina Winda; Mari'a, Dina Haniam; Sa'adah, Nila Lafifatus (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article discusses the historical role of Walisongo in developing a model of religious moderation in Indonesia. The aim is to understand more deeply the role and contribution of Walisongo in building inter-religious harmony and its relevance in the present context. The research method used is a literature study and qualitative approach by analyzing various literature sources related to the history of Walisongo and the concept of religious moderation in Islam. The discussion covers the historical background of the Walisongo, their role in shaping the concept of religious moderation, the values upheld in the Walisongo teachings, and the implementation of the Walisongo history-based religious moderation model in the context of modern Indonesia. This article shows that values such as tolerance, humanity, multicultural education, culture, nationality, wisdom, and peaceful behavior are important foundations in the development of a model of religious moderation in Indonesia. Through the implementation of these values, it is hoped that Indonesian society can achieve the goal of stronger national unity in the future.